“And they say that [they] worship stones”: Guaman Poma de Ayala and the discursive construction of Indigenous idolatries - León-Llerena, Laura (2020)
This essay studies Guaman Poma de Ayala’s narrative strategies to address ideas about materiality in Andean culture. It focuses on the descriptive systems and classifcations that are displayed along the Nueva corónica y buen gobierno to textually reconstruct the material dimension of what was called “idolatry”. The chronicler was Cristóbal de Albornoz’s assistant. Albornoz authored one of the frst treatises about the extirpation of idolatries. Guaman Poma included in his work information collected during his time with Albornoz about diverse objects that were classifed as idolatric. The Andean author agreed with Albornoz on the necessity to eradicate Indigenous objects and the rituals associated with them because these posed obstacles to the conversion of the Indians to Christianity. One can observe, however, that in Guaman Poma’s text there is a discursive tension that is absent in Albornoz’s writings. This is evidence of the resistant heterogeneity of Andean cultures before the homogeneizing process of discourses about “idolatries”.